Strategi Manajerial PT Timah Tbk (TINS) dalam Menghadapi Fluktuasi Harga Komoditas Global Industri Pertambangan - Sartini, Sartini; Dwi Astuti (GLOBAL SCIENTS PUBLISHER, 2025)
This research examines the global fluctuations of tin prices and its impact on PT Timah Tbk’s financial and operational performance in the year 2025. The study sought to focus on the effectiveness of managerial policies undertaken to deal with market pressures, limited reserves, external challenges, fierce competition in the export market, and the threat of illegal mining. This was accomplished through a combination of studying official financial documents, analyzing the price trend data from London Metal Exchange, and reviewing scholarly articles on mining company strategies. Findings indicate that PT Timah Tbk sustains competitiveness through cost-efficiency measures, digital optimization, market diversification, and strengthening global partnerships. These findings reinforce the notion that adaptive as well as innovative managerial strategies are vital to maintaining stability and sustainability amidst the volatility of the tin commodity industry.